Challenges and coping strategies: Perspectives of muslim international graduate students in Malaysian universities - Kamariah, Y.; Radzuwan, A.R.; Rahimah, E.; Mohd Anuwi, H. (2018)
This recent decade has observed an influx of Muslim students who migrate to other Muslim countries abroad to further their studies, mainly at postgraduate levels (Masters or Doctor of Philosophy). The influx of Muslim international postgraduate students potentially gives a positive impact on the migrated universities in terms of income generation. Malaysian public universities have received an increasing number of Muslim international postgraduate students registering each year, especially from the Middle East such as Jordan, Saudi Arabia, Iraq, Oman, Lebanon, Yemen, and a few others. Besides noticing the positive impact that these students have brought; that are, to promote Malaysia to become an Islamic educational tourism hub, little is known; however, about their struggles to meet the language barrier, academic challenges, and cultural barriers they face with the local community. To those universities that depend largely on the income generated from international students’ fees, the need to understand their problems, as well as to maintain this increasing figure earned each year is therefore urgent. This study aims to review the related literature pertaining to the challenges and perils experienced by Muslim international postgraduate students while undergoing their study at public universities in Malaysia, as well as to identify the coping strategies they have taken in meeting the challenges. This study is significant in terms of providing information to the top management of public universities in Malaysia in receiving international students.